Attentional bias for food cues in advertising among overweight and hungry children: An explorative experimental study. (January 2020) - Folkvord, Frans; Anschütz, Doeschka J.; Buijzen, Moniek
Highlights: This study examines if overweight and hungry children have an attentional bias. Measured in a food advertisement to guarantee ecological validity. Establishing individual susceptibility to food advertising. Overweight and hungrier children seem to be stronger affected by food advertising. Abstract: People with an increased motivation for rewarding substances show increased automatic selective attention towards cues that are related to that specific substance. The aim of this study was to explore if overweight and hungry children have an attentional bias for food cues in food advertising. A randomized between-subject design was used with 95 children who played an advergame that promoted either energy-dense snacks or non-food products. Overweight children had a higher gaze duration for the food cues compared to normal weight children. No effects were found of overweight on the attentional bias measurements for the non-food cues. Furthermore, hungrier children had a higher gaze duration, a higher number of fixations, and a faster latency of initial fixation on the food cues than less hungry children, while we found the opposite results for the non-food cues. The findings largely confirm our expectations, adding important knowledge about individual susceptibility to food advertisements. Overweight and hungrier children seem to be stronger affected by food advertising than normal weight and less hungry children. This study is the first that examined attentional bias in a food advertisement that is highly comparable to advertisements that are used by food companies, thereby increasing the external validity of the findings. The second strength is that the development of an attentional bias for food cues is developing at a young age and it was examined in a real-life situation.